Pengaruh Pemanfaatan Instagram @InfoUNP terhadap Kepuasan Pengguna Mahasiswa Departemen Ilmu Informasi Perpustakaan Universitas Negeri Padang - Gopinda, Marju; Nabila, Jeihan (ARZUSIN, 2024)
This study was conducted to determine the effect of Instagram @infounp utilization on user satisfaction of students of the Department of Information and Library Science, Faculty of Languages and Arts, Padang State University. This study consists of two variables, namely the Instagram utilization variable (X) with indicators of informative motives, educational motives, and entertainment motives and the user satisfaction variable (Y) with indicators of effectiveness, efficiency, and satisfaction. This research uses descriptive quantitative methods through questionnaires distributed to 100 respondents via Google Form. The population in this study were all Instagram followers @infounp. The data analysis technique used is the normality test and the 't' hypothesis test. Based on the results of the 't' test, it is known that the Instagram utilization variable (X) has an influence on user satisfaction (Y). This is based on the calculation that tcount 9.230> ttable 1.984. Then, the results also show that the utilization of Instagram @infounp is categorized as good so that it gives satisfaction to student users who are in the very good category.